A Molecular Phylogeny of Panax L. Genus (Araliaceae) Based on ITS-rDNA and matK Support for Identification of Panax Species in Vietnam - Thi Ngoc, Pham; Thanh Huyen, Pham; Quynh Nga, Nguyen; Van Truong, Phan; Minh Khoi, Nguyen; Doan Long, Dinh (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 36 No 2DO - 10.25073/2588-1132/vnumps.4198, 2020)
Panax L. is a small genus in the Araliaceae family. In Vietnam, this genus is distributed in the high mountains in the North and in some high mountains in the Central Highlands. In traditional medicine, roots and rhizomes of all Panax species are of high utility. Recently, the finding of new distributions of some Panax species in Vietnam has caused much controversy and confusion. This study investigates 27 fresh specimens of 6 taxa of Panax genus that have been collected from 6 provinces of Vietnam. Based on the combined ITS-rDNA and mat K dataset, a well-resolved phylogeny of Panax species/varieties distributed in Vietnam was constructed. Thereby, the study suggests identifying Tam that la xe as Panax stipuleanatus H.T.Tsai et K.M.Feng and Sam puxailaileng as Panax vietnamensis var. fuscidiscus K.Komatsu, S.Zhu & S.Q.Cai, which contributes a new distribution point of this variety in Vietnam. The study also shows that ITS-rDNA and mat K genes are highly potential in identifying and distinguishing the taxa of Panax genus. Keywords Panax , ginseng, molecular phylogeny, taxonomy, ITS-rDNA, mat K. References [1] Xiang, Q.B. & Lowry, P.P. Araliaceae, In: Wu, C.Y., Rawen, P.H. & Hong (2007). [2] Nguyen Tap, The species of Panax L. in Vietnam, Journal of Medicinal Material, 10 (3) (2005) 71-76 (in Vietnamese). [3] Phan Ke Long, Le Thanh Son, Phan Ke Loc, Vu Dinh Duy and Pham Van The, Lai Chau ginseng Panax vietnamensis var. fuscidiscus K. Komatsu, S. Zhu & S.Q. Cai.I. morphology, ecology, distribution and conservation status, Proceedings of the 2nd VAST – KAST workshop on biodiversity and bio-active compounds, Hanoi- Vietnam, October 28th – 29th (2013), pp. 65-73, Publishing house for science and technology. [4] Nong Van Duy, Le Ngoc Trieu, Nguyen Duy Chinh & Van Tien Tran, A new variety of Panax (Araliace) from Lam Vien Plateau, Vietnam and its molecular evidence, J. Phytotaxa 277(1) (2016) 047-058. http://dx.doi.org/10. 11646/ phytotaxa.277.1.4 [5] Tran Ngoc Lan et al., Results of study on Sam Puxailaileng in high moutain, Nghe An province, Nghe An journal of Science and Technology 12 (2016) 7-11 (in Vietnamese). [6] Do Huy Bich et al., Medicinal plant and animal in Vietnam, ep. II (2004), Science & Technic Pub. pp. 1255 (in Vietnamese). [7] X. Chen, B. Liao, J. Song, X. Pang, J. Han, S. Chen, A fast SNP identification and analysis of intraspecific variation in the medicinal Panax species based on DNA barcoding, Gene 530(1) (2013) 39-43. http://doi.org/10.1186/j.gene.2013.07.097 [8] Jun Wen and Elizabeth A. Zimmer, Phylogeny and Biogeography of Panax L. (the Ginseng Genus, Araliaceae): Inferences from ITS Sequences of Nuclear Ribosomal DNA, Molecular Phylogenetics and Evolution 6(2) (1996) 167-177. [9] C. Lee, J. Wen, Phylogeny of Panax using chloroplast trnC–trnD intergenic region and the utility of trnC–trnD in interspecific studies of plants, Mol Phylogenet Evol 31(2004): 894-903, DOI: 10.1016/j.ympev.2003.10.009 [10] Y. Zuo, Z. Chen, K. Kondo, T. Funamoto, J. Wen, S. Zhou, DNA barcoding of Panax species, Planta Med. 2011 Jan, 77(2) (2011):182-187. Doi: 0.1055/s-0030-1250166. [11] K. Komatsu, S. Zhu, S.Q. Cai, A new variety of the genus Panax from Southern Yunnan, China and its nucleotide sequences of 18S ribosomal RNA gene and matK gene, J. Jap. Bot 78(2) (2003) 86-94. [12] V. Manzanilla1, A. Kool, L. Nguyen Nhat, H. Nong Van, H. Le Thi Thu and H. J. de Boe, Phylogenomics and barcoding of Panax: toward the identification of ginseng species. BMC Evolutionary Biology (2018) 18-44. http://doi.org/10.1186/s12862-018-1160-y [13] Vu Huyen Trang, Hoang Dang Hieu, Chu Hoang Ha, Study on DNA barcode for identify Sam ngoc linh, National conference of biotechnology, Ep.2, (2013) 1100-1104. [14] Nguyen Thi Phuong Trang, Nguyen Thi Hong Mai, Zhuravlev Yury N, Reunova Galina D., rbcL and rpoB gene sequences of Panax vietnamensis var. fuscidiscus and Panax vietnamensis, the background for identification and comparison, Journal of Biology 39(1) (2016) 80-85. http://doi.org/10.15625/0866-7160/v39n1.7870 [15] Phan Ke Long, Tran Thi Viet Thanh, Nguyen Thien Tao, Phan Ke Loc, Nguyen Tu Lenh, Nguyen Tien Lam, Dang Xuan Minh, Morphological and molecular characsteristics of Panax sp. (Araliaceae) from Phu Xai Lai Leng mountain, Nghe An province, Vietnam, Journal of Biology 36(4) (2014) 494-499. https://doi.org/ 10.15625/0866-7160/v36n4.5212 [16] Phan Ke Long, Vu Dinh Duy, Phan Ke Loc, Nguyen Giang Son, Nguyen Thi Phuong Trang, Le Thi Mai Linh, Le Thanh Son, Phylogenetic relationships of the Panax samples collected in Lai Chau province based on matK and ITS-rDNA sequences, Journal of Biology 12(2) (2014) 327-337 (in Vietnamese). [17] Nguyen Thi Phuong Trang, Le Thanh Son, Nguyen Giang Son, Phan Ke Long, A new ginseng species Panax sp. (Araliaceae) in Vietnam, Journal of Pharmacology 10 (2011) 59-63. [18] Pham Thi Ngoc, Pham Thanh Huyen, Nguyen Quynh Nga, Nguyen Minh Khoi, Morphological characteristics of genus Panax L. (Araliaceae) in Vietnam, Journal of Medicinal Materials, 22(3) (2017) 315-322.